Clinical Immersion: An Approach for Fostering Cross-disciplinary Communication and Innovation in Nursing and Engineering Students. Issue 2 (March 2019) - Geist, Melissa J.; Sanders, Robby; Harris, Kevin; Arce-Trigatti, Andrea; Hitchcock-Cass, Cary
Abstract : Background: A faculty team from nursing and chemical engineering developed a course that brought together students from each discipline for cross-disciplinary, team-based clinical immersion and collaboration. Problem: Health care processes and devices are rapidly changing, and nurses are uniquely positioned to be bedside innovators to improve patient care delivery. Approach: During each clinical immersion, the student teams rotated through various hospital units where they identified problems and worked together in the university's makerspace (iMaker Space) to design and build prototypes to improve health outcomes. Outcomes: Data from the Critical thinking Assessment Test provided evidence of gains in critical-thinking and problem-solving skills, while the problems identified in the clinical setting and prototypes developed demonstrated the impact of bringing nursing and engineering students together to design innovations. Conclusions: When challenged to identify authentic problems during their clinical immersion, the teams of nursing and engineering students proposed creative solutions and developed commercially viable prototypes. Abstract : Supplemental digital content is available in the text.